Tilt Measurements in BMW Motorcycles - Łuczak, Sergiusz (Recent Global Research and Education: Technological Challenges, 2016)
Motorcycles are subjected to various orientation changes, both while riding as well as while parked (including pitch as well as roll angles). Equipping them with a tilt sensor, based e.g. on a micromachined accelerometer or gyroscope, provides many interesting possibilities. On one hand, the driver can be informed of results of measurements of various important parameters, which are disturbed by a tilt of the motorcycle. On the other hand, operation of various motorcycle control systems can be considerably improved and enhanced owing to tilt measurements. The existing applications of the measurements (anti-theft alarms, new generation of ABS systems) as well as possible options are surveyed, discussed and briefly analyzed.